EDUKASI PEMBUATAN DESAIN SEDERHANA MENGGUNAKAN APLIKASI CANVA - Salwa Alif Iwafani; Putri Ekaresty Haes (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The ability to master technology and information in this digitalization era is very necessary. The purpose of this activity is to provide insight into design for SMP Negeri 2 Susut students located in Abuan Village in using the Canva application. An effort to provide a way to make designs that are easy and attractive is to use an application that offers templates. With Canva, students can create with a selection of available templates, create posters, info graphics, logos and PowerPoints needed in today's learning systems. In carrying out this activity, the implementation was carried out using training methods and demonstrations to participants in using the Canva application. This educational activity was attended by around 50 participants from class IX students of SMP Negeri 2 Susut. The final result of this activity is that the participants have an overview of using Canva and the poster designs resulting from the creativity of the participants.